Spiritual and moral education of student youth in modern society - Jamalova , Gulnora Gulomovna (The Lingua Spectrum, 2026)
This article analyzes the key aspects of spiritual and moral education of student youth within the framework of a modern democratic society. In the context of ongoing democratization and liberalization processes, the formation of a well-rounded, socially responsible personality is considered one of the priority objectives of higher education. The study emphasizes the importance of fostering moral values, ethical behavior, and civic responsibility among students as essential components of sustainable social development. Special attention is paid to the role of continuous education in ensuring students’ moral maturity, enhancing their legal awareness, and broadening their worldview. The article highlights how educational institutions contribute to developing independent thinking, social adaptability, and professional competence among young people. Furthermore, the research examines the pedagogical and socio-economic factors influencing the formation of politically and legally literate youth capable of active participation in societal reforms. The author underlines that spiritual and moral education not only shapes students’ personal qualities but also strengthens their readiness to engage responsibly in socio-economic and political processes. The article concludes that cultivating moral stability, legal culture, and civic engagement among student youth plays a crucial role in building a democratic state based on the rule of law and long-term national development.